Respuestas

2012-06-27T20:05:41+02:00

. 1 . . . .2 . . . .1
------ + ----- = ------
. .3x. . . 5y. .. . 6

. 2. . . .. .3. . .. . . . 
------ -- ------ = 2 
. 3x. . . .. 4Y

Multiplico la 1ra por -2 para igualar las "x

- 2 . . . .4 . . . -2
------ -- ----- = ------
. .3x. . .. 5y. .. . 6

. 2. . . . . .3. . .. . 
------ -- ------ = 2
. 3x. . .. . 4Y

=========================== MCM entre 4y & 5y

-16-15 . . . 10
-----------= --------
. . 20y . . . . 6
==================================
-31*6=10*20y
==================================
-186=200y
==================================
-186/200=y y= -93/100
==================================

. 1 . . . . . . . .2 .. . . . . . . . .1
------ + ----------------- . . .= ------
. .3x. . ..5*(-93/100). . . . . . 6

==================================
5*(-93/100) = -465/100

simplificar por 5 queda...

-93/20
==================================

. 1 . . . . . . . .2 .. . . . . . . . .1
------ + ----------------- . . .= ------
. .3x. . . . .(-93/20). . . . . . . 6
==================================

2/(-93/20)= 2*(20/-93)= 40/-93
==================================
. 1 . . . . 40. . . . .1
------ + --------- = ------
. .3x. . . .-93 . . .. . 6
=================================
1. . . . .1 . . . . . .40
------ = ------ + -------
. 3x . . . 6 . . . . . 93
=================================
1. . . . .31+80
------ = -------------
. 3x . . . . . 186
=================================

186=3x*111
=================================
186=333x
=================================
186/333=x
=================================
62/111=x

ps creo que eso es! espero que este bn

2012-06-27T22:37:32+02:00

fàcil pz        4n          3n         2n          n                                                                                                  

               ax    +    bx     +   cx     +   dx   +  e

  si, n=1      4           3         2         1                                                                                        
              ax    +  bx    +    cx   +  dx     +   e

ejm:     4    2               4        3      2                                                                            
          x  + x  +1  =     x   +  0x  +  x   +  0x  +  1                                                                       

                                   2                                                                2                                     
                                 x               x                 1               se tiene: 2x        2             
                                  2                                                  se debe tener: x  
                                 x              -x                 1          2                 2                               
                                                                             (x  +  x  + 1)(x   -  x + 1)